Piezoelectric Polymer and Piezocapacitive Nanoweb Based Sensors for Monitoring Vital Signals and Energy Expenditure in Smart Textiles (Journal of Fiber Bioengineering and Informatics, 2013)
“Smart textiles”, also known as electronic or e-textiles contain embedded sensors capable of monitoringvital signals such as ECG, EMG, respiratory behaviour and are usually fabricated using rigidsemiconductors. In this study, we developed a flexible Physiological Sensing Belt (PSB) by embeddingsilicone rubber/carbon black/conductive carbon layer coated Polyvinylidene Fluoride (PVDF) filmbetween the elastic textile bands for monitoring respiration and the movement of thigh muscles. Withan average peak-to-peak interval of 3 sec, the respiration rate could be evaluated to be 20 min^{-1}. Wealso developed a novel hybrid sensor using PVDF and Thermoplastic Polyurethane (TPU) electrospunnanofiber webs stacked on each other and capable of measuring both static and dynamic pressuresimultaneously within all frequency ranges. Based on the samples used, we were able to measure thewalking speed of the subject at 4, 336 steps/h and 0.693 m/step at the speed of 3 km/h and with 6, 656steps/h and 0.751 m/step at the speed of 5 km/h. Overall, when compared to the existing commerciallyavailable pressure sensors, the PVDF and TPU nanofiber web based hybrid sensor developed in our studyhas advantages of high sensitivity, nanoscale thickness, lower hysteresis curve in pressure-capacitance,and can be easily converged with any fabric or textiles.
Keywords: Polyvinylidene Fluoride; Polyurethane; Electrospinning; Nanofiber Webs; Smart Textiles